1996
DOI: 10.1002/hep.510230545
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinase activation in hepatocyte growth factor-stimulated rat hepatocytes: Involvement of protein tyrosine kinase and protein kinase C

Abstract: MAP kinase activation in rat hepatocytes. Activation Received June 15, 1995; accepted December 18, 1995. of MAP kinases caused AA release, leading to producSupported in part by research grants from the Ministry of Education, Scition of prostaglandins (PGs), which promoted DNA synence, and Culture of Japan.Address reprint requests to: Takahito Adachi, M.D., Second Department thesis in rat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…They form tight colonies and upon stimulation with hepatocyte growth factor (HGF) cells at the edges migrate and the colonies consequently scatter. As expected, HGF was found to activate PLD in MDCK cells (Adachi et al, 1996) (data not shown). Addition of C 8 -PA resulted in formation of lamellipodia at the edges of colonies after 10-15 minutes and caused scattering of colonies that was similar to that seen upon addition of HGF (Fig.…”
Section: Journal Of Cell Science 119 (8)supporting
confidence: 84%
“…They form tight colonies and upon stimulation with hepatocyte growth factor (HGF) cells at the edges migrate and the colonies consequently scatter. As expected, HGF was found to activate PLD in MDCK cells (Adachi et al, 1996) (data not shown). Addition of C 8 -PA resulted in formation of lamellipodia at the edges of colonies after 10-15 minutes and caused scattering of colonies that was similar to that seen upon addition of HGF (Fig.…”
Section: Journal Of Cell Science 119 (8)supporting
confidence: 84%
“…The HGF receptor is the c-Met protein [4], and RPE cells express c-Met protein [16,26]. This protein is autophosphorylated upon HGF binding and interacts with intracellular proteins including Shc adapter [30], src [31], Grb [31], mitogen-activated protein kinases [1,6], phosphatidylinositol 3-kinase [6,31,32], protein kinase C [1,6] and phospholipase C-γ [31]. It will be interesting to clarify the signal that transduces the effect of HGF on occludin and epithelial morphogenesis of RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the mechanism of hepatocyte proliferation, we previously examined the signaling events in response to HGF using primary cultured rat hepatocytes [8][9][10][11] and found evidence that PGs, derived from arachidonic acid, and also probably DG from the PLD pathway, may play important roles in hepatocyte proliferation. Moreover, the importance of PLCδ4 was reported by Liu et al 37 In the present study, to verify the roles of the lipid-mediated signaling system during liver regeneration in vivo, the changes in mRNA and the protein levels of the involved enzymes were examined.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In fact, mice lacking HGF died with liver atrophy during the embryonic stage. 7 We previously examined the HGF-mediated signal transduction mechanism in rat primary cultured hepatocytes, [8][9][10][11] and found that the phospholipid signaling played important roles. The production of arachidonic acid metabolites and the activation of phospholipase D (PLD) were associated with DNA synthesis and the expression of c-fos and c-jun, respectively.…”
Section: Introductionmentioning
confidence: 99%